Rebranding Destination Branding of Pontianak - Tanjaya, Vania (Indonesian Journal of Visual Culture, Design, and Cinema, 2024)
Pontianak is known as a city where equator line crosses, this has been the identity of Pontianak over the past decades. Pontianak needs a branding rejuvenations as it has a lot to offer from culinary to its cultural events. This project discuss about the new brand identity made for Pontianak: Beyond Equator. The objectives is to help Pontianak in rejuvenate and rebrand their identity which in hope could gain exposure and attract more tourist. The method used in this project is qualitative method with Literature review, interviews with head of tourism department of Pontianak and a branding expert, and observational analysis on the city current conditions. The results is Pontianak has a lot to offer which does not translate in the current branding. Create a new brand identity that is contemporary but still hold the cultural root along the branding. The brand identity should be beneficial to the city alongside with an effective and strong promotional online and on-site.